Spatial Distribution of Stunting Incidence in the Highland Area of Tangse Subdistrict, Pidie Regency - Fitria Fitria; Frisca Fazira (UPT Publikasi Ilmiah Universitas Islam Bandung, 2026)
Stunting is a chronic nutritional issue and serves as a key indicator for assessing child health. Tangse Subdistrict, located in a highland area of Pidie Regency, shows a concerning prevalence of stunting among children. This study analyzed the spatial distribution of stunting cases in Tangse using GIS-based mapping technology. It was a descriptive observational study that utilized secondary data from the Tangse Health Center and was conducted from May to June 2025. The number of stunting cases per village was analyzed and mapped using ArcGIS (ArcMap v10.8) to visualize the spatial distribution by gender and age group. Stunting was found in twenty out of the twenty-eight villages in Tangse, with the highest incidence occurring in Gampong Pulo Baro at 10%. Furthermore, the prevalence was higher among boys (58%) than girls (42%). The age group most affected by stunting was children aged 12 to 23 months. The widespread occurrence of stunting across most villages may be linked to geographical barriers, limited access to health services, and differences in socio-economic and nutritional practices prevalent in highland areas. This study concludes that ArcGIS-based spatial analysis is effective in identifying high-risk areas and distribution patterns of stunting, which can support more targeted and evidence-based interventions at the community level. Further analysis of region-specific risk factors is needed to enhance targeted interventions in Tangse.